2022
DOI: 10.7759/cureus.23029
|View full text |Cite
|
Sign up to set email alerts
|

Hidradenitis Suppurativa: Estimated Prevalence, Clinical Features, and Risk Factors in Riyadh, Saudi Arabia

Abstract: BackgroundHidradenitis suppurativa (HS) is a chronic and recurrent inflammatory disease with a global prevalence of 1-4%, characterized by multiple painful nodules, abscesses, and fistulas that form scars in intertriginous regions (i.e., inguinal, axillary, mammary). HS is a complex and debilitating disease with a negative impact on quality of life. We aim to determine the prevalence, clinical features, risk factors, and comorbidities of HS. MethodologyA retrospective, descriptive, cross-sectional study was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…This allows physicians to follow disease progression and response to treatment [ 6 ]. The Sartorius score incorporates the visual pain scale and DLQI, which allows for the monitoring of disease severity and treatment response [ 5 , 23 ]. The Hidradenitis Suppurativa Clinical Response (HiSCR) is commonly used to evaluate response to treatment [ 23 ].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…This allows physicians to follow disease progression and response to treatment [ 6 ]. The Sartorius score incorporates the visual pain scale and DLQI, which allows for the monitoring of disease severity and treatment response [ 5 , 23 ]. The Hidradenitis Suppurativa Clinical Response (HiSCR) is commonly used to evaluate response to treatment [ 23 ].…”
Section: Reviewmentioning
confidence: 99%
“…A study assessing the quality of life of HS patients using the Dermatology Life Quality Index (DLQI) showed disease severity was correlated with higher DLQI scores and greater impairment [ 3 ]. The most commonly affected areas are intertriginous regions including the axilla, inframammary folds, inguinal region, and gluteal clefts [ 2 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These outbreaks mostly occur on body sites with skinto-skin contact, such as the axilla, groin, anogenital region and inframammary folds [2]- [4], [8]. Global prevalence estimates of HS range from 1-4% depending on several factors, such as ethnic background and the method of data collection [3], [5], [9], [10]. In general, women are more often affected by the disease compared to men in a ratio of 3:1 [11].…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis revealed that there are 118 760 093 HS cases reported in the literature 5. According to a study conducted in Riyadh, Saudi Arabia, the prevalence of HS was estimated to be 1.29%, and the most common accompanying disease was found to be diabetes mellitus type 2, followed by lipid disorders and acne 6. The treatment of HS is conducted on a long-term basis and is often challenging.…”
Section: Introductionmentioning
confidence: 99%